SHIP identifies genomic safe harbors in eukaryotic organisms using genomic general feature annotation - Matheus de Castro Leitão; Letícia Sousa Cabral; Luiza Cesca Piva; Pedro Felipe de Sousa Queiroz; Taísa Godoy Gomes; Rosângela Vieira de Andrade; Ana Laura Alfonso Perez; Karen Letycia Rodrigues de Paiva; Sônia Nair Báo; Viviane Castelo Branco Reis; Lídia Maria Pepe Moraes; Roberto Coiti Togawa; et al. (Scientific Reports)
Abstract Integrating foreign genes into loci, allowing their transcription without affecting endogenous gene expression, is the desirable strategy in genomic engineering. However, these loci, known as genomic safe harbors (GSHs), have been mainly identified by empirical methods. Furthermore, the most prominent available GSHs are localized within regions of high gene density, raising concerns about unstable expression. As synthetic biology is moving towards investigating polygenic modules rather than single genes, there is an increasing demand for tools to identify GSHs systematically. To expand the GSH repertoire, we present SHIP, an algorithm designed to detect potential GSHs in eukaryotes. Using the chassis organism Saccharomyces cerevisiae, five GSHs were experimentally curated based on data from DNA sequencing, stability, flow cytometry, qPCR, electron microscopy, RT-qPCR, and RNA-Seq assays. Our study places SHIP as a valuable tool for providing a list of promising candidates to assist in the experimental assessment of GSHs in eukaryotic organisms with available annotated genomes.